THE NEW UZBEKISTAN STRATEGY: NEW DIRECTIONS IN STATE POLICY IN THE FIELD OF TEACHING SOCIAL AND HUMANITARIAN SCIENCES IN THE PUBLIC EDUCATION SYSTEM - Yusupova Gulbaxor Turdiali qizi (Scholar Express Journal, 2023)
New Uzbekistan is taking a bold step towards achieving the standard of living among the developed countries of the world, building a fair, free and prosperous society, setting great goals and goals. Of course, we will not achieve this goal by ourselves. The development strategy is designed for 2022-2026 and envisages the implementation of the noble idea "For human dignity".
Keywords: Human dignity; development